Kayto wrote:1) Given f(x) = 2(squareroot of) x+1 and g(x) = (squareroot of) 2x-1 simplify 3(f+g)(2)

To learn how to "operate" on functions, try

**here**.

Then evaluate f(2) and g(2), add the results, and multiply by 3.

Kayto wrote:2) Given f(x) = 1-x^2 and g(x) = 2x + 1 evaluate (g . F) (-2)

Assuming "(g.F)" means

, then find g(-2) and f(-2), and multiply.

Kayto wrote:3) Given g(x) = (squareroot of) 3 - 2x and f(x) - |x-2| A) find g(f(x)) B) State if the composite functions exists

To learn how to compose functions, try

**here**.

Kayto wrote:4) Given f(x) = X /(2-x) and g (x) = 3/(x) A) Find (f . g) (x) B) State any restrictrions

Multiply the two rational expressions. Check for the x-values which would cause division by zero.

Kayto wrote:5) G(x) = (-3/5)x + 2 and its inverse.

To learn how to find inverse functions, try

**here**.